Padrão longitudinal da assembleia ictíica de um ribeirão do Sul do Brasil : uso da composição, estrutura, índices ecológicos e alimentação como instrumentos de avaliação da qualidade ambiental. - Novakowski, Gisele Caroline (2014)
The structure and composition of fish fauna was examined in seven stretches of the Pitangui river, Paraná State. These stretches are distinguished by degradation degree according to the chemical and physical evaluation of the habitat. The goal was to evaluate the role of composition and quantitative structure of fish fauna as indicators of environmental quality. The sites differ by riparian vegetation, substrate structure, and are exposed to different impacts from domestic and industrial sewage, pasture and agriculture. In this way, sites 1 and 2 were considered as more preserved stretches, and the other sites (3-7) as more impacted ones. Monthly samplings were conducted from April 2007 to May 2008. Forty-four fish species were identified; Characiformes and Siluriformes were the most representative orders in relation to species richness and abundance. The lowest and highest richness, with values corresponding to alpha diversity, probably represent the environmental conditions of the sites. The site 4 showed the lowest richness and diversity of species. Richness and abundance were significantly correlated with habitat descriptors. The abundance distribution of sites 3 and 4 showed better fit to geometric series, indicating that these were the most impacted locations. The other sites fitted to the log-normal model, indicated to slightly degraded communities. Our results point out that the physiography of each stretch has a strong influence on the quantitative structure of fish fauna, with higher richness and diversity at sites with greater structural complexity. In turn, changes in environmental quality due to human influence represented a key factor for composition and abundance of species therein. Thereby, ecological requirements of each species is probably what best define the structural patterns of the fish fauna from this environment. The analysis of stomach content of 28 species divided the fish fauna into 11 trophic groups. Aquatic insects were the most exploited resource, indicating a considerable representativeness of benthivorous species. Sites 6 and 7 showed the highest number of trophic groups. Piscivorous species were present in all sites, except for site 5. Non-significant trends for lower mean values of trophic niche breadth were detected for sites 3 and 4 (Ba<0.40) and for higher values for sites 1, 2 and 5 (0.40<Ba>0.60). Benthivorous species were absent at sites 5 and 6, but had important abundance and biomass at sites 3 and 4. Higher abundances of omnivorous species were found at sites 1, 5 and 6. Thereby, no significant association was verified between the generalism degree and preservation status of each stretch, but a trend for higher consumption of aquatic insects in the most impacted sites. Accordingly, the representativeness of benthivorous species, as for their biomass and abundance, appears to be an evidence of human impact.